Age-specific Distribution of Antimicrobial Use Surveillance using National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB Japan) 2011–2013. (4th October 2017) - Yamasaki, Daisuke; Tanabe, Masaki; Muraki, Yuichi; Kato, Genta; Yagi, Tetsuya
Abstract: Background: Antimicrobial use (AMU) surveillance is one of the key actions in the Japanese national plan on antimicrobial resistance (AMR). National database of health insurance claims and specific health checkups of Japan (NDB), which archives e-claim big data, is one candidate for their data source, since universal healthcare system is established in Japan and e-claim data covers almost all citizens. However, no study has been performed using NDB for assessing AMU. Our objective was to analyze the quantities and patterns of total systemic antibiotic prescriptions using NDB and to evaluate its utility. Methods: The data were analyzed in accordance with the Anatomical Therapeutic Chemical (ATC) classification using defined daily dose (DDD) as a measurement unit, as recommended by the WHO Collaborating Centre for Drug Statistics Methodology. The population-weighted total consumption was normalized and expressed as defined daily doses (DDDs) per 1000 inhabitants per day (DID). Trend analysis of DID from 2011 to 2013 and subgroup analysis stratified by age group (0–14, 15–64, 65 and above years old), and ATC classification were performed. Results: The DID value of oral antimicrobial use in 2013 was 13.2, which was a 1.04-fold increase in comparison with that in 2011. The DID value of parenteral antimicrobial use in 2013 was 0.83, which was a 1.13-fold increase in comparison with that in 2011. The DID value of each antibiotics category calculated using the NDB was comparable to that calculated using sales data in our previous study ( J Glob Antimicrob Resist. 7:19–23, 2016), suggesting that the NDB is useful for analyzing the quantities and patterns of total systemic antibiotic prescription. AMU in those under 15 years old decreased from 2011 to 2013 regardless of dosage form, although those in the other age groups increased. While third-generation cephalosphorins were the most frequently used oral antibiotic subgroups in those under 15 years old, macrolides were the most frequently used oral antibiotic subgroups in the other age groups. Conclusion: This is the first report evaluating age-specific distribution of AMU in Japan from 2011 to 2013 using the NDB. These results demonstrated the utility of AMU surveillance using the NDB as a tool and benchmark to assess the AMR action plan. Disclosures: All authors: No reported disclosures.